Integrating climate smart agriculture (CSA) into Turkana Agriculture Policy development - Ogutu, Elizabeth; Jalango, Dorcas; Ndetu, Veronica; Gamoyo, Majambo; Nzuki, Esther (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Turkana County’s agriculture sector faces escalating climate risks, including recurrent droughts, floods, and rising heat stress, threatening food security, livelihoods, and economic stability. Despite agriculture contributing significantly to the county’s GDP and employment, fragmented planning, weak institutional coordination, and donor-dependent financing have hindered the adoption of climate-smart agriculture (CSA). Key barriers include limited climate data, inadequate extension services, poor infrastructure, and exclusion of vulnerable groups from adaptation planning. This policy brief advocates for the integration of CSA into Turkana’s Agriculture Policy as a strategic framework to enhance resilience, productivity, and sustainability. CSA offers a transformative approach by aligning climate adaptation with economic development through practices such as drought-tolerant crops, efficient water management, rangeland restoration, and inclusive market development. The brief outlines actionable policy recommendations, including mandating climate risk assessments, strengthening institutional coordination, investing in ICT-enabled agro-advisories, and mobilizing climate finance through the County Climate Change Fund. By embedding CSA into county-level planning, Turkana can consolidate fragmented efforts, reduce climate vulnerability, and drive inclusive agricultural transformation.